Analisis Strategi Pemasaran Dalam Mengembangkan Umkm Toko Rifany Hijab - Vika Apriant; Ita Fatimah (LPPM Universitas Informatika dan Bisnis Indonesia, 2023)
The marketing strategy is one of the main functional strategies adopted by Micro, Small and Medium Enterprises (SMEs) to improve performance. The Community Service Program which was carried out within one semester tried to analyze the right marketing strategy for the development of a shop business that was developing in the fashion sector, namely Rifany Hijab. The method is carried out through four stages of analysis, namely environmental analysis, strategy planning (formulation), strategy implementation, and finally evaluation and control. The results of the analysis and formulation of the strategy show that Rifany Hijab has six internal key factors and six external key factors. Rifany Hijab's internal key factors consist of three strengths and three weaknesses, with the strength that has the highest score being the relatively cheap price of the product, and the weakness factor with the highest score being the working relationship between employees and superiors. Meanwhile, external factors Rifany Hijab has three opportunity factors and three threat factors, with the main opportunity being to participate in every promotional event and good customer service (Customer Service), as well as the main threat factor, namely the many competitors and newcomers of fellow hijab products and lots of price competition fellow hijab businessmen.